Peripheral Nervous System Involvement in Late-Onset Cobalamin C Disease? - Chu, Xujun; Meng, Lingchao; Zhang, Wei; Luo, Jinjun; Wang, Zhaoxia; Yuan, Yun (Frontiers in Neurology, 2020)
Background: Cobalamin C (cblC) has a fundamental role in both central and peripheral nervous system function at any age. Neurologic manifestations may be the earliest and often the only manifestation of hereditary or acquried cblC defect. Peripheral neuropathy remains a classical but underdiagnosed complication of cblC defect, especially in late-onset cblC disease caused by mutations in the methylmalonic aciduria type C and homocysteinemia (MMACHC) gene. So the clinical, electrophysiological and pathological characteristics of late-onset cblC disease are not well known. Methods: A retrospective study of patients with late-onset cblC disease was conducted at our hospital on a 3-year period. The neuropathy was confirmed by the nerve conduction study. Sural biopsies were performed in 2 patients. Results: Eight patients were identified, with a mean onset age of 16.25±6.07 years. All patients had methylmalonic aciduria, homocysteinemia, compound heterozygous MMACHC gene mutations were detected in all patients, and 7/8 patients with c.482G>A mutation. One patient concomitant with homozygote c.665C>T mutation in 5,10-methylenetetrahydrofolate reductase (MTHFR) gene. All patients showed limb weakness and cognitive impairment. Five patients had possible sensorimotor axonal polyneuropathy predominantly in the distal lower limbs. Sural biopsies showed loss of myelinated and unmyelinated fibers. Electro microscopy revealed crystalline-like inclusions bodies in Schwann cells and axonal degeneration. Conclusion: Late-onset cblC disease had possible heterogeneous group of distal axonal neuropathy. c.482G>A mutation is a hot spot mutation in late-onset cblC disease.